Enhancement of Science Studentsâ€™ Process Skills through Implementation of Green Learning Method (GeLem) with Conservation-Based Inquiry Approach - Savitri, E. N.; Wusqo, I. U.; Ardhi, M. W.; Putra, P. D. (Jurnal Pendidikan IPA Indonesia, 2017)
The inquiry of science teaching aims to encourage the ability to think, work and be scientific and communicate as an important aspect of life skills. Inquiry learning with Green Learning Method (GeLeM) focuses on the ability to think, work and be scientific. The data collection was conducted in the Department of Integrated Science, Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Semarang on the course of General Biology, even semester of the academic year 2016/2017. The results show that application of method â€œGeLeMâ€ can increase the average of cognitive value, learning response and the ability of studentsâ€™ Science Process Skill (SPS) in science learning especially biology in the material of the diversity of living creatures. Common biology lectures that use the method of Green Learning Method (GeLeM) can be collaborated with instilling conservation horizon on the students. The conclusion of this study is that Green Learning Method (GeLeM) can improve student cognitive result and science process skill in science learning. In addition, students are also able to find the concept that comes from the environment (nature), students can also love and care for the environment as a vehicle for learning.